STUDY ON ECONOMIC EFFICIENCY IN FLOWERCULTURE IN GREENHOUSES - A POPESCU (Journal of Central European Agriculture, 2003)
This study aimed to evaluate the economic efficiency in flowerculture in the greenhouses belonging to a private company next to the capital. The firm owns 2.45 ha greenhouses where it cultivates Fresia Species, Chrysanthemum Species and Alstroemeria Species. The average production was 1,200 thou Fresia flowers, 405 thou Chrysanthemum flowers and 610 thou Alstroemeria flowers/ha. All the three flower species assure a high economic efficiency, but Fresia is the most profitable one. It assures the highest profit per flower USD 0.023, the highest profit per hectar USD 28,576 and the highest profit rate 44 %. Then, in order are coming Alstroemeria and Chrysanthemum. These three species could represent the subject of a profitable productive activity for any floriculturist who would like to get secure incomes all over the year.